The rise of work-based academic education in Austria, Germany and Switzerland - Graf, Lukas [Verfasser] (My University, 2016)
"Austria, Germany and Switzerland are renowned for their extensive systems of collective vocational skill formation, which, however, have developed largely in separation from higher education. This divide has become increasingly contested as a result of a variety of socioeconomic factors that have led to an increasing demand for higher level skills. Do the three countries deal with these challenges in similar ways? The comparative analysis is based on process tracing from the 1960s to 2013 and builds on historical institutionalism as well as several dozen expert interviews with key stakeholders. A key finding is that all three countries have developed hybrid forms of work-based academic education that combine elements of vocational training and higher education. However, in Austria and Switzerland, these hybrids have been integrated into the traditional model of collective governance, whereas the German case signifies a departure from this model." (author's abstract; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 1.4 Hochschulbildung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2.1 Westeuropa; I 2.1 Deutschland; Berufsbildung; Hochschulbildung; Verzahnung beruflicher und hochschulischer Bildung; Dualer Studiengang; Vergleichende Bildungsforschung; Bundesrepublik Deutschland; Österreich; Schweiz